Prototype Charging Station Untuk Kendaraan Listrik Menggunakan Panel Surya 5WP - Maulana, Aldi Farid; Ibrahim, Ibrahim; Saragih, Yuliarman (Jurnal Ilmiah Wahana Pendidikan, 2023)
Kata kunci: Sel Surya, Charger, Arduino, Energi terbarukan Abstract Along with the development of the times, the increase in energy needs is getting higher, in contrast to the current availability of fossils which are continuously depleting and have the possibility that they will run out in time. This makes every human being obliged to think about what can be used as alternative renewable energy to support energy needs in the future. Currently, many solar panels have been developed that function as a conversion of sunlight into electrical energy, but have weaknesses at night. The main problem with this system is how to store the energy in the battery and how long it takes to charge and the power that can be provided by a 5WP panel from 8:00 to 17:00. The power generated will later be used to recharge the cellphone battery through a charging station system that will be made. The scope of this research is about utilizing sunlight to recharge the battery. This charger station is designed to use the Arduino microcontroller as the system control center. The method used is that the light received by the solar panels is converted into electrical energy and stored in a battery bank or main storage by a solar charger controller. From the battery, the current flows to each branch of the cellphone charger module. The test results can be concluded that the highest achievement was 53.28 watts from the first day to the third day of measurement and the highest achievement was 33.6 watts from the battery bank charging test by the panel. It can be concluded that the tool works according to its purpose. The choice of battery capacity and panel can support the need for a cellphone charger for 24 hours.